User experience testing methods: Conclusions from the literature - Koloszár, László; Bednárik, Éva; Erdős, Ferenc; Thinakaran, Rajermani; Takáts, Alexandra (Edelweiss Applied Science and Technology, 2024)
Industry 4.0 focuses on the digitalization of production processes and technological innovation. The concept of Industry 5.0 puts the focus on human-centricity, sustainability, and resilience at the heart of research and development and innovation (R&D&I) processes to allow industry to serve humanity with a long-term vision that considers planetary boundaries. Replacing the technology-driven approach with a fundamentally human-centric approach requires a deep understanding of the working environment and workers interacting with machines to optimize worker well-being, working conditions, and job outcomes. Analyzing computer work User eXperience (UX) in industrial environments is vital. However, user perceptions are usually hidden and a challenge to detect. Therefore, measuring and monitoring perceptions, emotional reactions, subjective elements, preferences, and attitudes in the relationships between usability, work performance, and workload is crucial. This study provides conclusions of a literature review on user experience studies focusing on UX testing methods and the disciplines linked to industrial diversification. Based on literature analysis, it identifies UX testing methods and create own grouping to analyze them. It also examines the disciplinary context of user experience testing.